Implementation of Accountability in the Management of PKU Muhammadiyah Sukoharjo Hospital - Pujiatmoko, Eko; Penatari, Resi Intan; Pamastutiningtyas, Terrensia Sekar; Jayanti, Suci (Jurnal Manajemen Dayasaing, 2024)
This research aims to explain the accountability of the management of the PKU Muhammadiyah Sukoharjo hospital from five aspects, namely legal and honesty aspects, process aspects, program aspects, policy aspects and financial aspects. This research uses a qualitative method from a phenomenological perspective. The data collection technique used was triangulation using in-depth interviews, observation and documentation. Data analysis was carried out in three stages, namely data reduction, data presentation, and drawing conclusions. The results of this research show that hospital management accountability. PKU Muhammadiyah Sukoharjo seen from the first five aspects, legal and honesty aspects states that there is no KKN at the employee, nurse and staff selection stage and carries out tasks in accordance with the established SOP. Second, aspects of the hospital program. PKU Muhammadiyah Sukoharjo provides training programs and workshops for doctors, nurses and other employees. The three aspects of the process indicate that the main tasks and functions have been carried out well, marked by appropriate service times according to procedures and affordable costs. Fourth, the policy aspect, policies made by the director such as costs, quality, SOPs that must be fulfilled. Fifth, financial accountability, there is no transparency regarding hospital financial reports. PKU Muhammadiyah Sukoharjo towards the community, apart from that there were no reports of hospital activity. PKU Muhammadiyah Sukoharjo therefore does not comply with the rules of PSAK No. 45 concerning financial reporting of non-profit organizations.